PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM UPAYA MENINGKATKAN MOTIVASI KERJA PEGAWAI PADA UNIT SDM BIRO AUK UIN SYARIF HIDAYATULLAH JAKARTA - Siti Fatimah; Yulies Herni (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This research aims to understand the perceptions of employees at the Human Resources Unit of the AUK Bureau of UIN Syarif Hidayatullah Jakarta regarding the meaning and concept of transformational leadership as well as how well it is implemented in improving work motivation. Transformational leadership is considered an important leadership style in organizations because it can provide inspiration, motivation, and positive changes for employees. This research uses a qualitative descriptive method with a phenomenological approach to explore the experiences and perspectives of informants in depth. Data collection techniques were conducted through observations and interviews. Data analysis was carried out using NVivo software to facilitate the process of systematic data processing and interpretation. The results of this study indicate that the concept and characteristics of transformational leadership, according to the informants, refer to a leadership style that is able to motivate, inspire, provide support, and give clear direction, thereby encouraging employees to improve their capabilities and overall quality in accordance with the organizational vision. In its implementation, leadership in the Human Resources Unit of the AUK Bureau has applied a transformational leadership style that plays a role in increasing employee work motivation. Therefore, transformational leadership plays an important role in creating a more productive work environment and supporting the achievement of organizational goals.